STUDI ANALISIS AKAD NIKAH MENGGUNAKAN VIDEO CALL PERSPEKTIF MAQOSHID AL-SYARIAH DAN UNDANG-UNDANG NO.1 TAHUN 1974 TENTANG PERKAWINAN - Amin, M. Misbahul (Prodi Ahwal al-Syakhsiyah STAI Darussalam Nganjuk, 2020)
In the analysis of maqasid al-shariah, the marriage contract with video call media at this time can be justified, but with some conditions that must be met such as the tools used and the network used can really be used to connect so that real-time maqshad is reached. that one method of maqoshid is to distinguish between maqshad and wasilah. In the perspective of Law No. 1 of 1974 concerning marriages, marriages by video call media are also considered marriages in the eyes of the legislation, as long as the implementation aims to form happy and eternal families (households) based on the divinity of the Almighty, or because they obey the commands of Allah SWT, or because aims to realize a sakinah, mawaddah, and mercy household life.